Teachers’ Perceptions of the Identification Process and Implementation of Individualized Education Programs for Special Needs Students in Elementary Schools - Hanrezi Dhania Hasnin; Rasmitadila; Annisa Mawardini; Nabila Kamaliah; Syahara Putri Kholifah (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Identifying and developing Individualized Education Programs (IEPs) are essential steps in providing appropriate educational services for students with special needs. However, in practice, not all schools that enroll students with special needs possess the knowledge or ability to identify these needs and create effective IEPs. Consequently, educational services for these students are often considered less than optimal. This study aims to explore teachers' perceptions of students with special needs and the implementation of identification and IEP processes in schools. The participants were teachers at SDN Rangga Mekar, Bogor City, a school that has not been officially designated as inclusive but has enrolled students with special needs. The results indicated that while most teachers recognized the importance of inclusive and specialized educational approaches, only a few had sufficient knowledge regarding student needs assessment and the development of IEPs. Data showed that 90% of teachers acknowledged the necessity of differentiated education to optimize student potential. However, only 63% understood the concept of needs identification, 36% were familiar with IEPs, and none had experience creating an IEP for a student. Teachers' perceptions of students with special needs varied, influenced by their individual levels of knowledge and experience. Nonetheless, teachers expressed optimism that, with the right strategies, students with special needs could develop successfully. This study highlights the urgent need for additional training and resources to strengthen teachers' competencies in supporting students with special needs, thereby fostering a more inclusive learning environment.